Analisis Kepuasan Aplikasi ULA (Untung Lancar Aman) Metode UTAUT Pada UMKM Jombang: Analysis of ULA Application Satisfaction (Profit Smoothly Safe) UTAUT Method in Jombang MSMEs - Kaasto, Darojat; Murtadho, Mohamad Ali; Wafa, Moh. Shohibul (AMIK, 2023)
Information systems have become an urgent need for groups of people, including Micro, Small and Medium Enterprises (MSMEs) who are online or e-commerce traders. The availability of the ULA (Lucky Current and Safe) application managed by PT Jembatan Akar Teknologi is an example of e-commerce that makes life easier for MSMEs. The ULA App is a multi-category B2B e-commerce marketplace that offers MSME businesses access to cutting-edge retail equipment, technology and experiences. To gather opinions and answers from users of the ULA application targeting MSMEs in Jombang City regarding the efficacy and satisfaction of using a system, researchers in this study used the UTAUT approach. By sharing the Google From link either directly or via the WA group,amounting to 80 respondents calculated using SPSS16 software. User satisfaction with the ULA Jombang application is only obtained from the Facilitation Condition variable, not from the Performance Expectation, Business Expectation or Social Influence factors based on the results of data processing. The level of user satisfaction with the Facilitating Conditions factor meets the convenience indicators, namely requirements that facilitate user satisfaction and are in line with the needs of ULA Jombang application users. Based on hypothesis testing, each UTAUT variable influences how satisfied users are with the ULA application.